Extended-Reach Drilling (ERD)—The Main Problems and Current Achievements - Karim El Sabeh; Nediljka Gaurina-Međimurec; Petar Mijić; Igor Medved; Borivoje Pašić (Applied Sciences, 2023)
With the development of different segments within the drilling technology in the last three decades, well drilling has become possible in harsh downhole conditions. The vertical well provides access to oil and gas reserves located at a certain depth directly below the wellsite, and a large number of vertical wells are required for the exploitation of hydrocarbons from spatially expanded deposits. However, the borehole can deviate from the vertical well, which means that the target zone can be reached by a horizontal directional well. With this type of well, especially in the case of drilling an extended-reach well (ERW), the length of the wellbore in contact with the reservoir and/or several separate reservoirs is significantly increased, therefore, it is a much better option for the later production phase. Unfortunately, the application of extended-reach drilling (ERD technology), with all of its advantages, can cause different drilling problems mostly related to the increased torque, drag, hole cleaning and equivalent circulation density (ECD), as well as to an increase in the well price. Overcoming these problems requires continuous operational change to enable operators to address downhole challenges. Today, the longest well reaches 15,240 m (50,000 ft), which raises the question of the technological and economic feasibility of this type of drilling project, especially with the lower oil price on the energy market. This paper provides a comprehensive overview of extended-reach drilling technology, discusses the main problems and analyzes current achievements.